2020
DOI: 10.1029/2019gl085311
|View full text |Cite
|
Sign up to set email alerts
|

Predictability Horizons in the Global Carbon Cycle Inferred From a Perfect‐Model Framework

Abstract: On interannual timescales the growth rate of atmospheric CO 2 is largely controlled by the response of the land and ocean carbon sinks to climate variability. Yet, it is unknown to what extent this variability limits the predictability of atmospheric CO 2 variations. Using perfect-model Earth System Model simulations, we show that variations in atmospheric CO 2 are potentially predictable for 3 years. We find a 2-year predictability horizon for global oceanic CO 2 flux with longer regional predictability of up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…Given the longer predictive horizons of the ocean carbon sink (in the models which provided output from both the ocean and the land biogeochemistry components), our results indicate that predictability of the atmospheric CO 2 growth in these models is limited by the land carbon sink predictability. Analogously, a previous study, based on a perfect model framework (Spring & Ilyina, 2020), demonstrates that the predictive skill of atmospheric CO 2 concentration of 3 years is dampened by land.…”
Section: Predictability Of Carbon Sinks and Atmospheric Co2 Growth Ratesupporting
confidence: 61%
See 1 more Smart Citation
“…Given the longer predictive horizons of the ocean carbon sink (in the models which provided output from both the ocean and the land biogeochemistry components), our results indicate that predictability of the atmospheric CO 2 growth in these models is limited by the land carbon sink predictability. Analogously, a previous study, based on a perfect model framework (Spring & Ilyina, 2020), demonstrates that the predictive skill of atmospheric CO 2 concentration of 3 years is dampened by land.…”
Section: Predictability Of Carbon Sinks and Atmospheric Co2 Growth Ratesupporting
confidence: 61%
“…On the land side, a potential prediction skill of 2 years was established for terrestrial net ecosystem production (Lovenduski, Bonan, et al., 2019), but only of 9 months for tropical land‐atmosphere carbon flux (Zeng et al., 2008). Perfect‐model frameworks based on idealized simulations suggest analogous predictability horizons for the carbon sinks (Séférian et al., 2018; Spring & Ilyina, 2020). However, previous studies were either limited to internally consistent model environments of perfect models (Frölicher et al., 2020; Séférian et al., 2018; Spring & Ilyina, 2020) or single initialized models (Fransner et al., 2020; Li et al., 2019, 2016; Lovenduski, Yeager, et al., 2019; Krumhardt et al., 2020; Yeager et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have found increases in ozone in populated urban areas during lockdown (e.g., Keller et al., 2020), in contrast to a global decrease in tropospheric ozone (Weber et al., 2020). This MIP provides an opportunity to shed process‐level understanding on these changes in a range of models of varying degrees of complexity with regards to atmospheric chemistry. Impact on the global carbon cycle : There is increasing interest in the ability to make predictions from one year to the next of changes in atmospheric CO 2 (Betts et al., 2016; Fransner et al., 2020; Lovenduski et al., 2019; Séférian et al., 2018; Spring & Ilyina, 2020). These studies require knowledge of natural causes of interannual variability, notable from ENSO (Watanabe et al., 2020), but they also require knowledge of up to date estimates of anthropogenic CO 2 emissions.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade SMILEs have been increasingly utilised in climate science (e.g. Zelle et al, 2005;Branstator and Selten, 2009;Kay et al, 2015;Frankignoul et al, 2017;Kirchmeier-Young et al, 2017;Sanderson et al, 2018;Stolpe et al, 2018;Maher et al, 2019;Deser et al, 2020). The value of SMILEs comes from the ability to quantify and separate the internal variability of the climate system and the forced response to changes in external forcing (e.g.…”
Section: An Introduction To Smilesmentioning
confidence: 99%